Binaphthyl monomer and preparation method thereof, epoxy resin and preparation method thereof and application thereof
Through the synthesis and crosslinking technology of binaphthalene monomer, the problem of low thermal conductivity of existing liquid crystal epoxy resins is solved, and epoxy resins with high thermal conductivity and good mechanical properties are achieved, which are suitable for electronic devices.
Patent Information
- Application Number
- CN202211686490.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The existing liquid crystal epoxy resin prepared with a rigid structure with benzene ring or biphenyl group as the core has low thermal conductivity and is difficult to meet the needs of high thermal conductivity materials.
Binaphthalene monomer is used as a new monomer, and the reaction of 1,1'-binaphthalene and 6-bromo-1-hexene in the presence of alkali is carried out, and then oxidized with peroxide to form a binaphthalene structure. epoxy resin and crosslink with the curing agent to form a material with good thermal conductivity and mechanical properties.
The thermal conductivity and mechanical properties of epoxy resin are improved, the thermal conductivity reaches more than 0.24W/(m·K), and the tensile break strength and elongation of break also reach more than 35.4MPa and more than 1.02%, which is suitable for electronic devices.
Smart Images

Figure CN116063252B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer chip packaging materials, and in particular to a binaphthyl monomer and a preparation method thereof, and an epoxy resin and a preparation method and application thereof. Background Art
[0002] With the development of modern electronic technology, heat generation has become an important factor limiting the performance of electronic devices. Therefore, higher demands are placed on thermal conductive materials in industry and the market. At present, there are two main methods to improve the thermal conductivity of polymer-based composite materials. One is to achieve thermal conductivity by adding thermally conductive fillers to the matrix resin, that is, filled thermal conductivity; the other is to achieve thermal conductivity by improving the thermal conductivity of the polymer itself, that is, intrinsic thermal conductivity. Generally speaking, the improvement of the thermal conductivity of filled composite materials is achieved by adding a large amount of inorganic fillers, which is bound to have a negative impact on the mechanical properties and electrical properties of the material. Therefore, in recent years, researchers have begun to turn their attention to the research and development and manufacture of intrinsic thermal conductive materials. Among them, improving the order and crystallinity of the epoxy resin molecular chain is one of the most controllable methods to improve the intrinsic thermal conductivity of epoxy resin, which is usually achieved by introducing a liquid crystal structure of benzene rings or biphenyl groups.
[0003] Liquid crystal epoxy resin prepared with a rigid structure based on benzene rings or biphenyl groups is a highly ordered, deeply cross-linked polymer network. It has the characteristics of liquid crystal order and high network cross-linking, and can significantly improve its intrinsic thermal conductivity on the basis of traditional epoxy resin. However, the thermal conductivity of liquid crystal epoxy resin prepared with a rigid structure based on benzene rings or biphenyl groups is still relatively low. Therefore, synthesizing new intrinsic high thermal conductivity epoxy resins through molecular design is an important idea to improve the thermal conductivity of epoxy resin matrix. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of low thermal conductivity of epoxy resin prepared with a rigid structure with a benzene ring or a biphenyl group as the core in the prior art, and to provide a binaphthyl monomer and a preparation method thereof, an epoxy resin and a preparation method and application thereof. The epoxy resin prepared from the binaphthyl monomer has better thermal conductivity and mechanical properties.
[0005] In order to achieve the above object, the present invention provides a first aspect of a binaphthyl monomer, which is a monomer represented by formula (I),
[0006]
[0007] A second aspect of the present invention provides a method for preparing a binaphthyl monomer, comprising the following steps:
[0008] (1) in the presence of a base, 1,1'-bi-2-naphthol and 6-bromo-1-hexene are subjected to a first reaction to obtain compound 1;
[0009] (2) subjecting compound 1 to a second reaction with a peroxide to obtain a binaphthyl monomer represented by formula (I),
[0010]
[0011] The third aspect of the present invention provides an epoxy resin, which contains structural units from the monomers provided by the present invention; the epoxy resin has a thermal conductivity of more than 0.24 W / (m·K), a tensile strength at break of more than 35.4 MPa, and a tensile elongation at break of more than 1.02%.
[0012] A fourth aspect of the present invention provides a method for preparing an epoxy resin, comprising the following steps: mixing a monomer and a curing agent to perform a curing reaction to obtain the epoxy resin;
[0013] Wherein, the monomer is the naphthalene ring monomer provided by the present invention or the binaphthyl monomer prepared by the preparation method provided by the present invention.
[0014] A fifth aspect of the present invention provides an application of the epoxy resin provided by the present invention or the epoxy resin prepared by the preparation method provided by the present invention in electronic devices.
[0015] Through the above technical solution, the beneficial effects of the present invention are:
[0016] Compared with the prior art, the present invention uses 1,1'-binaphthol as a reaction raw material and adopts a binaphthol structure for synthesis. Compared with the benzene ring, the electron cloud of the condensed ring of the naphthalene ring makes it easier to produce a "π-π" self-assembly effect. At the same time, the binaphthol structure can form a liquid crystal structure in a shorter chain segment period, thereby better improving the orderliness of the prepared resin and the thermal conductivity of the epoxy resin. At the same time, the epoxy resin also has good mechanical properties.
[0017] In a preferred embodiment of the present invention, by further selecting a suitable ratio of 1,1'-bi-2-naphthol, 6-bromo-1-hexene and alkali, a suitable type of dispersant and polymerization inhibitor, and a suitable ratio of dispersant, polymerization inhibitor and 1,1'-bi-2-naphthol, the yield and purity of the monomer are further improved. In addition, the present invention further selects a suitable type of curing agent, a suitable ratio of monomer to curing agent, and suitable curing conditions, so that the prepared epoxy resin has more excellent thermal conductivity and mechanical properties. In addition, adding a suitable amount of boron nitride during curing can further improve the thermal conductivity of the epoxy resin. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] The first aspect of the present invention provides a binaphthyl monomer, which is a monomer represented by formula (I),
[0020]
[0021] A second aspect of the present invention provides a method for preparing a binaphthyl monomer, comprising the following steps:
[0022] (1) in the presence of a base, 1,1'-bi-2-naphthol and 6-bromo-1-hexene are subjected to a first reaction to obtain compound 1;
[0023] (2) subjecting compound 1 to a second reaction with a peroxide to obtain a binaphthyl monomer represented by formula (I),
[0024]
[0025] According to the present invention, preferably, in step (1), the first reaction is carried out in the presence of a dispersant and an inhibitor.
[0026] Preferably, the dispersant is selected from at least one of polyethylene glycol, polyvinyl pyrrolidone, triethylhexyl phosphate, sodium lauryl sulfate and methylpentanol, preferably polyethylene glycol, more preferably polyethylene glycol 400.
[0027] Preferably, the polymerization inhibitor is selected from at least one of hydroquinone, p-tert-butylcatechol and p-hydroxyphenyl ether, and is preferably a mixture of p-hydroxyphenyl ether and hydroquinone.
[0028] Furthermore, the weight ratio of p-hydroxyphenyl ether to hydroquinone is (10-12): 1. When the weight ratio of p-hydroxyphenyl ether to hydroquinone in the polymerization inhibitor meets the above range, it is possible to avoid premature over-reaction of the reactants to generate other products, thereby being able to produce high-purity monomers, and then the epoxy resin obtained by curing the monomers with a curing agent has better thermal conductivity and mechanical properties. If it is not within this range, the yield and purity of the monomers will be reduced, and the reduction in the purity of the monomers will affect the thermal conductivity and mechanical properties of the cured epoxy resin.
[0029] According to the present invention, preferably, the base is selected from sodium hydroxide and / or potassium carbonate, preferably sodium hydroxide.
[0030] According to the present invention, preferably, step (1) further comprises: separating and drying the compound, and the separation may be performed by vacuum filtration.
[0031] According to the present invention, preferably, in step (2), the peroxide is selected from at least one of meta-chloroperbenzoic acid, hydrogen peroxide, dibenzoic acid peroxide and methyl percarbonate, preferably meta-chloroperbenzoic acid.
[0032] According to the present invention, preferably, step (2) further comprises: before the second reaction, dissolving the compound 1 in an organic solvent.
[0033] According to the present invention, preferably, the organic solvent is selected from at least one of acetone, toluene, n-hexane, cyclohexane, ethyl acetate and dichloromethane, preferably dichloromethane.
[0034] According to the present invention, preferably, step (2) further comprises: extracting, washing and purifying after the compound reacts with the peroxide.
[0035] According to a specific embodiment of the present invention, the extraction can be performed by mixing the product after the reaction with a saturated NaHCO3 solution, and then extracting with dichloromethane; the washing detergent can be brine; the drying desiccant can be anhydrous magnesium sulfate; and the purification can be performed by column chromatography using ethyl acetate-hexane (ethyl acetate-hexane volume ratio is 5:95).
[0036] According to the present invention, preferably, in step (1), the weight ratio of 1,1'-bi-2-naphthol, 6-bromo-1-hexene and the base is 1:(1-4):(0.1-0.4).
[0037] According to the present invention, preferably, in step (1), the weight ratio of the dispersant, the polymerization inhibitor and 1,1'-bi-2-naphthol is 1: (0.2-0.4): (85-90). When the weight ratio of the dispersant, the polymerization inhibitor and 1,1'-bi-2-naphthol meets the above range, a large amount of resin monomers can be successfully synthesized to ensure that the monomers have a high yield and purity. If it is not within this range, it will lead to a decrease in the monomer yield and purity, thereby affecting the thermal conductivity and mechanical properties of the cured epoxy resin.
[0038] According to the present invention, preferably, the weight ratio of the compound 1 to the peroxide in step (2) is 1:(1-3).
[0039] According to the present invention, preferably, in step (1), the temperature of the first reaction is 50° C.-70° C., and the time of the first reaction is 2-5 h.
[0040] More preferably, in step (1), the temperature of the first reaction is 60°C-62°C, and the time of the first reaction is 2.5-3h.
[0041] According to the present invention, preferably, the temperature of the second reaction in step (2) is 20° C.-30° C., and the time of the second reaction is 1-3 h.
[0042] More preferably, in step (2), the temperature of the second reaction is 25°C-27°C, and the time of the second reaction is 1.5-2h.
[0043] The third aspect of the present invention provides an epoxy resin, which contains structural units derived from the monomers provided by the present invention;
[0044] The epoxy resin has a thermal conductivity of more than 0.24 W / (m·K), a tensile strength at break of more than 35.4 MPa, and a tensile elongation at break of more than 1.02%.
[0045] A fourth aspect of the present invention provides a method for preparing an epoxy resin, comprising the following steps: mixing a monomer and a curing agent to perform a curing reaction to obtain the epoxy resin;
[0046] Wherein, the monomer is the binaphthyl monomer provided by the present invention or the binaphthyl monomer prepared by the preparation method provided by the present invention.
[0047] The principle of preparing the epoxy resin of the present invention is: 1,1'-binaphthol and 6-bromo-1-hexene are reacted under the action of a base to obtain a binaphthol compound, then the double bonds in the binaphthol compound are oxidized into epoxy groups by peroxide, and then a curing agent is selected for curing and cross-linking, and the epoxy end group and the active hydrogen of the amino group of the curing agent undergo a ring-opening reaction, and the resin is connected and cured to form a resin. At the same time, the binaphthol structure in the monomer undergoes a π-π self-assembly effect, and under the constraint of a flexible chain, an orderly oriented structural micro-region is formed to obtain a liquid crystal phase structure, thereby improving the orderliness inside the resin, so that the obtained epoxy resin has good thermal conductivity and mechanical properties.
[0048] According to the present invention, preferably, the mixing is performed using a planetary mixer, the mixing speed is 1800-2100 r / min, the time is 350-450 s, and the temperature is 20°C-35°C.
[0049] According to the present invention, preferably, the curing agent is an amine curing agent.
[0050] Preferably, the curing agent is selected from at least one of 4,4-diaminodiphenylmethane, 4,4-diaminodiphenyl ether, 4,4-diaminodiphenyl sulfone, 4-methyl-metaphenylenediamine and ethylenediamine, preferably 4,4-diaminodiphenylmethane and / or 4,4-diaminodiphenyl sulfone, more preferably a mixture of 4,4-diaminodiphenylmethane and 4,4-diaminodiphenyl sulfone.
[0051] Furthermore, the weight ratio of 4,4-diaminodiphenylmethane to 4,4-diaminodiphenyl sulfone is (1-4): 1. When the weight ratio of 4,4-diaminodiphenylmethane to 4,4-diaminodiphenyl sulfone in the curing agent meets the above range, the monomer can obtain a better curing effect, so that the cured epoxy resin has better thermal conductivity and mechanical properties. If it is not within this range, it will make the curing reaction difficult to proceed, thereby affecting the mechanical properties and thermal conductivity of the epoxy resin.
[0052] According to the present invention, preferably, the weight ratio of the monomer to the curing agent is (2-5):1.
[0053] According to the present invention, preferably, the temperature of the curing reaction is 150° C. to 270° C., and the time of the curing reaction is 2-8 hours.
[0054] More preferably, the temperature of the curing reaction is 175° C.-180° C., and the time of the curing reaction is 3-4 hours.
[0055] According to the present invention, preferably, the method further comprises the following steps: mixing the monomer, the curing agent and the boron nitride, and then performing a curing reaction to obtain the epoxy resin. Adding boron nitride helps to improve the performance of the epoxy resin, improve its thermal conductivity and electrical insulation performance under high temperature conditions.
[0056] Preferably, the weight ratio of boron nitride to the monomer is (0.2-0.5): 1. When the weight ratio of boron nitride to the monomer meets the above range, the thermal conductivity of the resin can be further improved. If it is not within this range, the curing difficulty will be increased.
[0057] More preferably, the weight ratio of boron nitride to the monomer is (0.3-0.4):1.
[0058] A fifth aspect of the present invention provides an application of the epoxy resin provided by the present invention or the epoxy resin prepared by the preparation method provided by the present invention in electronic devices.
[0059] Example 1
[0060] Preparation of monomers:
[0061] 100 mL of water, 0.032 g of polyethylene glycol 400 and 0.01 g of p-hydroxyphenyl ether were added to the reaction container, and 0.8 g of NaOH was slowly added under stirring to form a uniform dispersion. 2.86 g of 1,1'-bi-2-naphthol was added to the above dispersion, and after sufficient stirring, 3.26 g of 6-bromo-1-hexene was added, and the mixture was stirred at 60°C for 3 h, filtered and dried to obtain the compound.
[0062] 50mL of dichloromethane was added to the reaction vessel to dissolve the compound, and then meta-chloroperbenzoic acid was added dropwise so that the weight ratio of the compound to meta-chloroperbenzoic acid was 1:1, and the mixture was stirred at 25°C for 2 hours. After the reaction was completed, the mixture was poured into a saturated NaHCO3 solution and extracted with dichloromethane. The combined organic layer was washed with brine and dried with anhydrous MgSO4. The crude product was purified by column chromatography using ethyl acetate-hexane (volume ratio 5:95) to obtain a monomer. The mass of the obtained monomer was measured to obtain a monomer yield of 78.2wt%, and the purity of the monomer was 83.6wt% as measured by liquid chromatography-mass spectrometry.
[0063] Preparation of epoxy resin:
[0064] 5 g of monomer and 1.6 g of 4,4-diaminodiphenylmethane were placed in a material cup and stirred in a planetary stirring system at a stirring speed of 2000 r / min, a time of 400 s, and a temperature of 25° C. The mixture obtained above was placed in a mold and placed in a drying oven for curing at 180° C. for 4 hours to obtain an epoxy resin material.
[0065] Example 2
[0066] Preparation of monomers:
[0067] 150 mL of water, 0.048 g of polyethylene glycol 400 and 0.01 g of p-hydroxyphenyl ether were added to the reaction container, and 0.8 g of NaOH was slowly added under stirring to form a uniform dispersion. 4.29 g of 1,1'-bi-2-naphthol was added to the above dispersion, and after sufficient stirring, 4.89 g of 6-bromo-1-hexene was added, and stirred at 60°C for 3 hours, filtered and dried to obtain the compound.
[0068] 50 mL of dichloromethane was added to the reaction vessel to dissolve the compound, and then meta-chloroperbenzoic acid was added dropwise so that the weight ratio of the compound to meta-chloroperbenzoic acid was 1:2, and the mixture was stirred at 25 ° C for 2 hours. After the reaction was completed, the mixture was poured into a saturated NaHCO3 solution and extracted with dichloromethane. The combined organic layer was washed with brine and dried with anhydrous MgSO4. The crude product was purified by column chromatography using ethyl acetate-hexane (volume ratio 5:95) to obtain a monomer. The yield of the monomer measured according to the assay method of Example 1 was 78.9wt%, and the purity was 86.7wt%.
[0069] Preparation of epoxy resin:
[0070] 5 g of monomer, 1.6 g of 4,4-diaminodiphenylmethane and 1.5 g of boron nitride were placed in a material cup and stirred in a planetary stirring system at a stirring speed of 2000 r / min, a time of 400 s and a temperature of 25° C. The mixture obtained above was placed in a mold and placed in a drying oven for curing at 180° C. for 4 h to obtain an epoxy resin material.
[0071] Example 3
[0072] The epoxy resin was prepared according to the preparation method of Example 2, except that 2 g of boron nitride was added during the preparation of the epoxy resin to obtain the epoxy resin.
[0073] Example 4
[0074] The epoxy resin was prepared according to the preparation method of Example 1, except that in the process of synthesizing the monomer, the proportions of polyethylene glycol 400 (dispersant), p-hydroxyphenyl ether (inhibitor) and 1,1'-bi-2-naphthol were different, and 0.032g of polyethylene glycol 400, 0.02g of p-hydroxyphenyl ether and 3.72g of 1,1'-bi-2-naphthol were added to obtain the monomer. The yield of the monomer was measured by the determination method of Example 1 to be 75.1wt% and the purity was 82.6wt%.
[0075] Example 5
[0076] The epoxy resin was prepared according to the preparation method of Example 1, except that in the process of synthesizing the monomer, 0.0092 g of p-hydroxyphenyl ether and 0.0008 g of hydroquinone were used as polymerization inhibitors to obtain the monomer. The yield of the monomer was 81.2 wt % and the purity was 88.3 wt % as measured by the determination method of Example 1.
[0077] Example 6
[0078] The epoxy resin was prepared according to the preparation method of Example 5, except that in the process of synthesizing the monomer, the polymerization inhibitor was selected from 0.005 g of p-hydroxyphenyl ether and 0.005 g of hydroquinone to obtain the monomer. The yield of the monomer was measured according to the determination method of Example 1, and the purity was 79.1 wt % and 84.7 wt %.
[0079] Example 7
[0080] The epoxy resin was prepared according to the preparation method of Example 1, except that 1.04 g of 4,4-diaminodiphenylmethane and 0.56 g of 4,4-diaminodiphenyl sulfone were used as the curing agent.
[0081] Example 8
[0082] The epoxy resin was prepared according to the preparation method of Example 7, except that 0.6 g of 4,4-diaminodiphenylmethane and 1.0 g of 4,4-diaminodiphenyl sulfone were used as the curing agent.
[0083] Example 9
[0084] The epoxy resin was prepared according to the preparation method of Example 1, except that the curing conditions were: curing at 200° C. in an oven for 6 h.
[0085] Comparative Example 1
[0086] 5 g of 4,4'-di(5,6-epoxyhexyloxy)biphenyl and 1.6 g of 4,4-diaminodiphenylmethane were placed in a material cup and stirred in a planetary stirring system at a stirring speed of 2000 r / min, a time of 400 s, and a temperature of 25° C. The mixture obtained above was placed in a mold and placed in a drying oven for curing at 180° C. for 4 hours to obtain an epoxy resin material.
[0087] Comparative Example 2
[0088] 5 g of 4,4'-bis(5,6-epoxyhexyloxy)biphenyl, 1.6 g of 4,4-diaminodiphenylmethane and 1.5 g of boron nitride were placed in a material cup and stirred in a planetary stirring system at a speed of 2000 r / min, a time of 400 s and a temperature of 25° C. The mixture obtained above was placed in a mold and placed in a drying oven for curing at 180° C. for 4 h to obtain an epoxy resin material.
[0089] Comparative Example 3
[0090] 5 g of 4,4'-di(5,6-epoxyhexyloxy)biphenyl, 1.6 g of 4,4-diaminodiphenylmethane and 2 g of boron nitride were placed in a material cup and stirred in a planetary stirring system at a speed of 2000 r / min, a time of 400 s and a temperature of 25° C. The mixture obtained above was placed in a mold and placed in a drying oven for curing at 180° C. for 4 h to obtain an epoxy resin material.
[0091] Test Case
[0092] The thermal conductivity and mechanical properties of the epoxy resins prepared in the examples were measured. The test results of each example are shown in Table 1.
[0093] Thermal conductivity test method: A thermal conductivity meter was used to test the thermal conductivity of the epoxy resin material. The French SETARAM transient plane heat source method (TPS) was used to detect the thermal conductivity. The sample thickness was 2.4 mm.
[0094] Method for breaking strength test: A universal tensile testing machine is used to test the breaking strength of the sample to be tested, with a tensile speed of 50 mm / min, and a tensile test length and width of 50 mm and 5 mm respectively.
[0095] Method for elongation at break test: A universal tensile testing machine is used to test the elongation at break of the sample to be tested, the tensile speed is 50 mm / min, and the length and width of the tensile test are 50 mm and 5 mm respectively.
[0096] All tests were performed at room temperature.
[0097] Table 1
[0098] Breaking strength / MPa Elongation at break / % Thermal conductivity W / (m·K) Example 1 87.7 1.85 0.27 Example 2 43.5 1.21 2.41 Example 3 35.4 1.02 3.02 Example 4 81.5 1.78 0.24 Example 5 92.3 1.95 0.3 Example 6 79.6 1.62 0.24 Example 7 89.6 1.86 0.3 Example 8 82.8 1.69 0.24 Example 9 83.7 1.80 0.25 Comparative Example 1 76.4 1.67 0.19 Comparative Example 2 25.6 1.03 1.44 Comparative Example 3 23.4 0.96 1.86
[0099] It can be seen from the results in Table 1 that compared with comparative examples 1-3, the epoxy resin synthesized by using 1,1'-bi-2-naphthol as the reaction raw material and the binaphthol structure in the present invention has significantly improved mechanical properties and thermal conductivity compared with the epoxy resin synthesized by using the benzene ring structure. In Examples 2 and 3, different weights of boron nitride were added respectively, and the mechanical properties of the epoxy resins obtained were slightly reduced, but the thermal conductivity was improved.
[0100] In addition, Example 4 changes the ratio of dispersant, polymerization inhibitor and 1,1'-bi-2-naphthol. Compared with Example 1, the yield and purity of the obtained monomer are reduced to a certain extent, and the mechanical properties and thermal conductivity of the obtained epoxy resin are also reduced to a certain extent; Example 9 changes the curing conditions. Compared with Example 1, the mechanical properties and thermal conductivity of the obtained epoxy resin are reduced to a certain extent; the polymerization inhibitor of Example 5 uses 0.0092g of p-hydroxyphenyl ether and 0.0008g of hydroquinone. Compared with Example 1, the yield and purity of the obtained monomer are improved to a certain extent, and the mechanical properties and thermal conductivity of the obtained epoxy resin are also improved; Example 6 The ratio of p-hydroxyphenyl ether to hydroquinone is not within the preferred range. Compared with Example 5, the yield and purity of the obtained monomer are reduced to a certain extent, and the mechanical properties and thermal conductivity of the obtained epoxy resin are also reduced to a certain extent; the curing agent in Example 7 uses 1.04g of 4,4-diaminodiphenylmethane and 0.56g of 4,4-diaminodiphenyl sulfone. Compared with Example 1, the mechanical properties and thermal conductivity of the obtained epoxy resin are improved; the ratio of 4,4-diaminodiphenylmethane to 4,4-diaminodiphenyl sulfone in Example 8 is not within the preferred range. Compared with Example 7, the mechanical properties and thermal conductivity of the obtained epoxy resin are reduced to a certain extent.
[0101] It can be seen that the type of inhibitor, the ratio of each component in the inhibitor, and the ratio of dispersant, inhibitor and 1,1'-bi-2-naphthol have a great influence on the yield and purity of the monomer, thereby affecting the mechanical properties and thermal conductivity of the epoxy resin. In addition, the type of curing agent, the ratio of each component in the curing agent, and the curing conditions will affect the mechanical properties and thermal conductivity of the epoxy resin. This shows that the process of synthesizing the monomer and the curing process jointly affect the thermal conductivity and mechanical properties of the epoxy resin obtained.
[0102] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A binaphthyl monomer, characterized in that: The monomer is a monomer represented by formula (I), 2. A method for preparing a binaphthyl monomer, characterized in that: The following steps are involved: (1) in the presence of a base, subjecting 1,1'-bi-2-naphthol and 6-bromo-1-hexene to a first reaction to obtain compound 1, wherein the first reaction is carried out in the presence of a dispersant and an inhibitor, wherein the weight ratio of the dispersant, the inhibitor and 1,1'-bi-2-naphthol is 1:(0.2-0.4):(85-90), and the inhibitor is selected from at least one of hydroquinone, p-tert-butylcatechol and p-hydroxyphenyl ether; (2) subjecting compound 1 to a second reaction with a peroxide to obtain a binaphthyl monomer represented by formula (I), 3. The preparation method according to claim 2, characterized in that: The dispersant is selected from at least one of polyethylene glycol, polyvinyl pyrrolidone, triethylhexyl phosphoric acid, sodium lauryl sulfate and methyl amyl alcohol; And / or, the base is selected from sodium hydroxide and / or potassium carbonate.
4. The preparation method according to claim 3, characterized in that: The base is sodium hydroxide.
5. The preparation method according to claim 3, characterized in that: The dispersant is polyethylene glycol; And / or, the inhibitor is a mixture of p-hydroxyphenyl ether and hydroquinone.
6. The preparation method according to claim 5, characterized in that: The weight ratio of p-hydroxyphenyl ether to hydroquinone is (10-12):
1.
7. The preparation method according to claim 2 or 3, characterized in that: In step (2), the peroxide is selected from at least one of meta-chloroperbenzoic acid, hydrogen peroxide, dibenzoic acid peroxide and methyl percarbonate; And / or, step (2) further comprises: before the second reaction, dissolving the compound 1 in an organic solvent.
8. The preparation method according to claim 7, characterized in that: The peroxide is meta-chloroperbenzoic acid; And / or, the organic solvent is selected from at least one of acetone, toluene, n-hexane, cyclohexane, ethyl acetate and dichloromethane.
9. The preparation method according to claim 8, characterized in that: The organic solvent is dichloromethane.
10. The preparation method according to claim 3, characterized in that: In step (1), the weight ratio of 1,1'-bi-2-naphthol, 6-bromo-1-hexene and the base is 1:(1-4):(0.1-0.4); And / or, in step (2), the weight ratio of compound 1 to peroxide is 1:(1-3).
11. The preparation method according to claim 2, characterized in that: In step (1), the first reaction temperature is 50°C-70°C, and the first reaction time is 2-5h; And / or, in step (2), the second reaction temperature is 20°C-30°C, and the second reaction time is 1-3h.
12. An epoxy resin, characterized in that The epoxy resin contains structural units derived from the monomers of claim 1; The epoxy resin has a thermal conductivity of more than 0.24 W / (m·K), a tensile strength at break of more than 35.4 MPa, and a tensile elongation at break of more than 1.02%.
13. A method for preparing an epoxy resin, characterized in that: The method comprises the following steps: mixing a monomer and a curing agent to perform a curing reaction to obtain the epoxy resin; Wherein, the monomer is the binaphthyl monomer described in claim 1 or the binaphthyl monomer prepared by the preparation method described in any one of claims 2-11.
14. The preparation method according to claim 13, characterized in that: The curing agent is an amine curing agent; and / or, the weight ratio of the monomer to the curing agent is (2-5):1; And / or, the curing reaction temperature is 150°C-270°C, and the curing reaction time is 2-8h; And / or, the method further comprises the following steps: mixing the monomer, the curing agent and the boron nitride, and then curing to obtain the epoxy resin.
15. The preparation method according to claim 14, characterized in that: The curing agent is selected from at least one of 4,4-diaminodiphenylmethane, 4,4-diaminodiphenyl ether, 4,4-diaminodiphenyl sulfone, 4-methyl-metaphenylenediamine and ethylenediamine.
16. The preparation method according to claim 15, characterized in that: The curing agent is selected from 4,4-diaminodiphenylmethane and / or 4,4-diaminodiphenyl sulfone.
17. The preparation method according to claim 16, characterized in that: The curing agent is a mixture of 4,4-diaminodiphenylmethane and 4,4-diaminodiphenyl sulfone.
18. The preparation method according to claim 17, characterized in that: The weight ratio of 4,4-diaminodiphenylmethane to 4,4-diaminodiphenylsulfone is (1-4):
1.
19. The preparation method according to claim 14, characterized in that: The weight ratio of boron nitride to the monomer is (0.2-0.5):
1.
20. Use of the epoxy resin according to claim 12 or the epoxy resin prepared by the preparation method according to any one of claims 13 to 19 in electronic devices.
Citation Information
Patent Citations
Diepoxy compound, process for preparation thereof, and compositions containing the diepoxy compound
WO2011078099A1